POSISI TIDUR MIRING 30 DERAJAT TERHADAP TERJADINYA LUKA TEKAN PADA PASIEN STROKE DI RSUD SIDOARJO - Marsaid Marsaid; Hurun Ain; Fauzia Isma Wazida (Poltekkes Kemenkes Malang, 2019)
Stroke is a cerebrovascular disease causes brain tissue death. Brain tissue death causes a neurological deficit so it will be weakness of muscle tone and impaired physical mobility that causes the patient to be immobilized and should bed rest. Long bed rest can cause pressure with continously, it will cause tissue intolerance and pressure wounds. This research aims to determine the effect of 30 degrees laterally sleeping position against occurrence pressure ulcers in stroke patients at RSUD Sidoarjo. The design of this research using Pre experimental design with Static Group Comprism design. The sampling technique used was Non Probability Sampling with the number of respondents 34 people that is 17 people in the treatment group who were given intervention of 30 degrees laterally sleeping position and 17 people in the control group who were not given intervention of 30 degrees laterally sleeping position, but still given standard intervention from the room as it should. Then will be observed the occurrence of wound press (post test). The result of research with Mann Whitney Test got p value 0,016, meaning that there was a significant difference in the occurrence of pressure ulcers between the treatment group and the control group at the final observation. This research concludes that there is an effect of 30 degrees laterally sleeping position against occurrence pressure ulcers in stroke patients. From the results of this reaearch is expected intervention can be used as a prevention strategy of pressure ulcers. Keywords: 30 degrees laterally sleeping position, Pressure ulcers, Stroke